Analisis Kualitas Website Pesona Karanganyar Menggunakan Metode WebQual 4.0 - Tri Romadloni, Nova; Hana Mulia, Pamela; Nova Ellyanza, Marcellina; Nurul Iksani, Salma; Rianti , Ria; Rahmawati, Aderima (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
The Pesona Karanganyar website serves as an information platform accessible to all users without limitations. This official website provides comprehensive information about tourism destinations, events, and available facilities. It aims to deliver an informative and interactive experience for users, making it easier for them to plan trips and explore the beauty of Karanganyar. To provide excellent service to potential visitors, it is crucial to enhance the website's quality by assessing user satisfaction, identifying existing issues, and considering improvements for future development. This study evaluates the quality of the Pesona Karanganyar website using the WebQual 4.0 method. Data collection was conducted through surveys using a Google Form questionnaire based on WebQual dimensions, involving a total of 60 respondents. The validity and reliability of the data were tested as prerequisites. Data analysis involved calculating scores and averages for each indicator. The results of this analysis indicate that the usability, information quality, and interaction quality variables of the Pesona Karanganyar website are of good quality. These findings suggest that the Department of Tourism, Youth, and Sports of Karanganyar Regency should regularly evaluate the website's maintenance and development to improve the quality of its services.